Alone - Chaboute 1967-; Hahnenberger, Ivanka (New York Gallery 13, 2017)
""On a tiny lighthouse island far from the rest of the world, a lonely hermit lives out his existence. Every week a supply boat leaves provisions, its occupants never meeting him, never asking the obvious questions: Who are you? Why do you hide? Why do you never leave? What is it like to be so alone? Years spent on a deserted rock--a lifetime, really--with imagination his sole companion has made the lighthouse keeper something more than alone, something else entirely. For him, what lies beyond the horizon might be...nothing. And so, why not stay put? But one day, as a new boatman starts asking the questions all others have avoided, a chain of events unfolds that will irrevocably upend the hermit's solitary life" -- provided by publisher.
"Originally published in French in 2008 by Editions Glénat SA as Tout Seul"--Title page verso.
Keywords: Graphic novels; Comic books, strips, etc; Translations